A General Overview of Enforcement in Civil and Commercial Matters in Macedonia - Zoroska-Kamilovska Tatjana; Rakočević, Milka (LeXonomica, 2017)
The paper discusses one of the currently most relevant topics in the area of civil law protection in the Republic of Macedonia. In 2005 Macedonia made a drastic step in reforming the system of civil enforcement: the previous court-oriented system of enforcement was replaced with the bailiff-oriented system. The enforcement procedure has ceased of being under the jurisdiction of the court and the enforcement was entrusted to enforcement agents - persons with public authorizations established by law, who conduct the enforcement. With the introduction of the new system of civil enforcement Macedonia strove to eliminate all dysfunctionalities of the system due to the slowness and the inefficiency of the enforcement procedure, which seriously affected the proper administration of justice. The paper gives a general overview regarding the Macedonian civil enforcement system with special emphasis on certain issues that are considered to be of major importance, such as the reforms that were implemented or being implemented regarding the system of civil enforcement, the legal basis of enforcement, the status and role of the enforcement agents in the legal system of the Republic Macedonia, the institutional framework, structure and order of the enforcement proceedings, the enforcement titles, as well as the issue regarding the means of enforcement and the distinction between enforcement and security measures.